Bleeding after endoscopic sphincterotomy or papillary balloon dilation among users of antithrombotic agents - Hamada, Tsuyoshi; Yasunaga, Hideo; Nakai, Yousuke; Isayama, Hiroyuki; Matsui, Hiroki; Horiguchi, Hiromasa; Fushimi, Kiyohide; Koike, Kazuhiko (Endoscopy, 2015)
Background and study aims: Severe bleeding is a potentially lethal complication after endoscopic sphincterotomy (EST) and endoscopic papillary balloon dilation (EPBD) for choledocholithiasis. This study aimed to evaluate the impact of antiplatelet agents and anticoagulants on this complication.Patients and methods: Patients who underwent EST and EPBD were identified in a Japanese nationwide administrative database covering 1090 hospitals. Adjusting for other potential risk factors, we evaluated the association between oral administration of antiplatelet agents and/or anticoagulants (continuation, discontinuation, and non-use) and clinically significant bleeding within 3 days of the procedure.Results: In total, 61 002 patients were analyzed (EST, 54 493 patients; EPBD, 6509). The rate of severe bleeding was 0.8 % in both groups, but EPBD was performed more frequently than EST in patients with chronic renal failure, liver cirrhosis, and in those receiving antiplatelet agents or anticoagulants. The impact of continuation/discontinuation of antiplatelet agents on severe bleeding was not statistically significant in the EST or EPBD groups. The use of anticoagulants was associated with a statistically significant increase in severe bleeding compared with non-use for EST (1.6 % 27 of 1688 patients vs. 0.8 % 429 of 52 805 patients; adjusted odds ratio [OR] 1.70; 95 % confidence interval [CI] 1.10 – 2.63) and for EPBD (3.0 % [8 of 263 patients] vs. 0.7 % 46 of 6246 patients; adjusted OR 2.91; 95 %CI 1.36 – 6.24).Conclusions: EST and EPBD can be safely performed in patients receiving antiplatelet agents. Users of anticoagulants are at high risk of bleeding, and the periprocedural management of these should be further investigated.